A survey of quality of life among elderly population in Yogyakarta: A questionnaire-based study - Dani Hanif Koncoro; Susi Ari Kristina (Journal of Global Pharma Technology, 2020)
Indonesia, as one of the world's developing countries, faced a demographic transition. Indonesian people's life expectancy has risen over time. It imposed the escalating elderly population in Indonesia. Quality of Life ( QoL) was an important assessment to be measured in the elderly as many comorbidities involved. This research aimed at determining QoL among the elderly population and QoL-related factors. A questionnaire-based survey was conducted among 210 elderly participants attending Yogyakarta's Elderly Community Services (Poslansia). QoL was evaluated using WHOQOL-BREF. Socio-demographic variables were analyzed using a questionnaire. Data was analyzed using SPSS version 22. QoL score differences among elderly characteristics were analyzed using Mann Whitney test. QoL score among respondents showed dimensions of social relationships had the lowest score among domains (QoL score 46.78 ± 10.72). Participants with spouses had better QoL scores than widowed participants (p 0.032). Participants who had better QoL scores than smoker participants (p